2022
DOI: 10.3788/col202220.041101
|View full text |Cite
|
Sign up to set email alerts
|

Deep learning-based scattering removal of light field imaging

Abstract: Light field imaging has shown significance in research fields for its high-temporal-resolution 3D imaging ability. However, in scenes of light field imaging through scattering, such as biological imaging in vivo and imaging in fog, the quality of 3D reconstruction will be severely reduced due to the scattering of the light field information. In this paper, we propose a deep learning-based method of scattering removal of light field imaging. In this method, a neural network, trained by simulation samples that a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 35 publications
0
1
0
Order By: Relevance
“…The complex targets were used as the test set. Neural network training was performed to decouple the data and extend them to localize targets of complex objects [33][34][35][36][37][38][39][40]. Experimental results indicated that unknown Photonics 2022, 9, 956 3 of 15 target localization of speckle images was achieved by addressing the limitations of massive datasets, categories, and target shape desensitization.…”
Section: Introductionmentioning
confidence: 99%
“…The complex targets were used as the test set. Neural network training was performed to decouple the data and extend them to localize targets of complex objects [33][34][35][36][37][38][39][40]. Experimental results indicated that unknown Photonics 2022, 9, 956 3 of 15 target localization of speckle images was achieved by addressing the limitations of massive datasets, categories, and target shape desensitization.…”
Section: Introductionmentioning
confidence: 99%